2014
DOI: 10.1177/1039856214533395
|View full text |Cite
|
Sign up to set email alerts
|

A state-wide quality improvement system utilising nurse-led clinics for clozapine management

Abstract: Differing interpretations of clozapine guidelines have contributed to confusion around monitoring. Standardised documentation has helped to increase understanding and improve protocol adherence. A regular training programme has increased basic knowledge of risks and protocols. Computer-based documentation and alerting systems have improved communication between hospital and community-based teams and prompted early intervention reducing the risk of adverse events. These factors have combined to help improve out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
5
0
2
Order By: Relevance
“…The CDST may be an effective way to improve clinician adherence to the prescribing and monitoring guidelines for patients prescribed clozapine. This is consistent with other studies that have shown brief monitoring guidelines can improve clinician knowledge and behaviour . The CDST could be included in national guidelines for the safe and quality use of clozapine and a laminated hardcopy could be kept in the ward with the patient's medication chart, available to doctors, nurses and pharmacists as a quick reference guide to best practice.…”
Section: Discussionsupporting
confidence: 79%
“…The CDST may be an effective way to improve clinician adherence to the prescribing and monitoring guidelines for patients prescribed clozapine. This is consistent with other studies that have shown brief monitoring guidelines can improve clinician knowledge and behaviour . The CDST could be included in national guidelines for the safe and quality use of clozapine and a laminated hardcopy could be kept in the ward with the patient's medication chart, available to doctors, nurses and pharmacists as a quick reference guide to best practice.…”
Section: Discussionsupporting
confidence: 79%
“…Beyond the above-mentioned possible reasons for variations in clozapine use by country, time, sex or age, the question remains, how to increase clozapine prescribing rates to a satisfactory level? A significant lead towards an answer is provided by recent research: over the last years, several interventions designed to increase clozapine use in patients with TRS have been successfully evaluated (67)(68)(69)(70). While these interventions employ very different approaches, for example specialist-led outpatient clinics for patients with suspected TRS (67), a combination of clinical guidelines with practical clozapine titration schemes, a clozapine information brochure for patients and finger-prick tests for haematological monitoring (70), a statewide implementation of a clozapine management system centred around nurse-led clinics, including standardised clozapine documentation and GP education packages (69), and state-wide action plans, feedback and internet-based educational programmes (68), all of them have succeeded in increasing the rates of TRS patients receiving clozapine.…”
Section: Age and Gender Differences In Clozapine Usementioning
confidence: 99%
“…There is some evidence that educational interventions improve the rates and quality of Clozapine prescriptions. These educational interventions include Dutch [6] , US [7], Australia [8] and New Zealand [9] examples. The content of these educational interventions vary but essentially cover following aspects: increased training in clozapine in identifying suitable patients for clozapine, education in side effects management, developing and implementing standardised protocols for medical review, supporting documentation and adverse event management, shared decision making and training in use of point care devices However laudable and effective these interventions are, they remain isolated efforts, that are not supported by educational institutions.…”
Section: Schizophreniamentioning
confidence: 99%